Implementation of PBL in undergraduate thinking and communication skills course: The UM experience - Arshad, M. (2002)
The implementation of problem based learning in undergraduate thinking and communication skills course is a recent move by the University of Malaya to improve its student's ability to think and communicate effectively. This move was associated with the philosophy of the university to face the challenge of preparing students who are able to meet the needs of the real "world" when they graduated from the university. The aim of this paper is to discuss changes in the respective roles and belief of teachers and students about teaching and learning in an interactive environment. This papers discusses preparation of PBL packages, tutors training workshop, implementation of PBL curriculum in the thinking and communication skills course, issues of evaluation and students assessment, and challenges faced by the university in the implementation of the curriculum.